Analisis Penentuan Zonasi Rawan Kebakaran Hutan dan Lahan di Wilayah Cilegon - Novita Himawati; Yayat Ruhiat; Rudi Haryadi (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
Cilegon City is one of the cities in Banten Province with an altitude between 0-500 meters above sea level. Cilegon city consists of eight sub-districts namely Pulomerak, Grogol, Purwakarta, Jombang, Citangkil, Cilegon, Ciwandan and Cibeber. Based on the Cilegon city BNBD data, forest and land fire disasters increased in 2023. Forest and land fires are one of the more frequent phenomena. The negative impacts of forest and land fires include ecological damage, decline in the economic value of forests and soil productivity, decline in biodiversity, micro or global climate change and smoke disrupting air, land and sea transportation. To prevent the occurrence of forest and land fires in the Cilegon City area, it is necessary to have a map that can declare forest and land fire prone zones by taking into account rainfall, soil type, and land cover factors. The purpose of this research is to map forest and land fire prone zones as an effort to support the realization of forest fire management strategies in the Cilegon City area by taking into account rainfall, soil type, and land cover factors.